Preventive effects of nerve growth factor against colistin-induced autophagy and apoptosis in PC12 cells. (24th March 2019) - Tian, Erjie; Hu, Wanjun; Miao, Yusong; Muhammad, Ishfaq; Zhang, Ling; Xia, Chunli; Ding, Liangjun; Zhang, Qiaomei; Li, Rui; Chen, Chunli; Li, Jichang
Abstract: In this study, the preventive effects of NGF against colistin-induced autophagy and apoptosis in PC12 cells have been investigated. Fluorescence microscopy, real-time PCR, transmission electron microscopy (TEM), flow cytometery, and western blotting technique were used. The results showed that large amounts of autophagosomes and apoptotic markers were triggered by colistin. Consistently, a significant increase has been noted at mRNA and protein levels in autophagy and apoptosis-related genes. Besides, TEM analysis showed that autophagic vacuoles were obvious at 12 h, while nuclear chromatin condensation and edge accumulation were clearly seen at 24 h in colistin alone group. Importantly, the visual autophagy and apoptosis were markedly reduced with NGF treatment in a dose-dependent manner. Moreover, colistin-induced reduction in mitochondrial membrane potential was partly attenuated by NGF in a dose dependent manner. In summary, NGF ameliorated colistin-induced apoptosis and autophagy, and partially recovered MMP in PC12 cells.